Skill Downgrading among Refugees and Economic Immigrants in Germany: Evidence from the Syrian Refugee Crisis - Plamen Nikolov; Leila Salarpour Goodarzi; David Titus (Institute of Labor Economics (IZA), 2022)
Upon arrival to a new country, many immigrants face job downgrading, a phenomenon describing workers being in jobs far below where they would be assigned based on their skills. Downgrading leads to immigrants receiving lower returns to the same skills than natives. The level of downgrading could depend on the type of immigrant and numerous factors. This study examines the determinants of skill downgrading among two types of immigrants – refugees and economic immigrants – in the German labor markets between 1984 and 2018. We find that refugees downgrade more than economic immigrants, and this discrepancy between the two groups persists over time. We show that language skill improvements exert a strong influence on subsequent labor market outcomes of both groups.
Keywords: J11; J15; J61; F22; O15; J61; 330; downgrading; immigrants; refugees; Germany; labor markets; wages; employment